2019
DOI: 10.1111/iju.14076
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future perspective of robot‐assisted radical cystectomy for invasive bladder cancer

Abstract: The current status of robot‐assisted radical cystectomy was reviewed 16 years after the initial robot‐assisted radical cystectomy for the treatment of invasive bladder cancer. Articles associated with robot‐assisted radical cystectomy and written in English were selected from the PubMed database from January 2003 to February 2019. The present review article focused on the distribution of robot‐assisted radical cystectomy, patient selection, preoperative management, surgical technique, lymph node dissection, ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 91 publications
(171 reference statements)
2
16
0
Order By: Relevance
“…The survival rate of LRC in the present study was almost comparable to that of MIRC (LRC or RARC) or that of ORC, as previously reported . In accordance with our results, systemic reviews and recent randomized trials for RARC have shown that oncological outcomes of MIRC are equivalent to those of ORC . Similar to previous reports, 5‐year relapse‐free survival, cancer‐specific survival and overall survival were stratified into pT and pN, and the presence or absence of lymph node dissection, pT and pN were significant factors associated with recurrence on multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The survival rate of LRC in the present study was almost comparable to that of MIRC (LRC or RARC) or that of ORC, as previously reported . In accordance with our results, systemic reviews and recent randomized trials for RARC have shown that oncological outcomes of MIRC are equivalent to those of ORC . Similar to previous reports, 5‐year relapse‐free survival, cancer‐specific survival and overall survival were stratified into pT and pN, and the presence or absence of lymph node dissection, pT and pN were significant factors associated with recurrence on multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…[11][12][13] In accordance with our results, systemic reviews and recent randomized trials for RARC have shown that oncological outcomes of MIRC are equivalent to those of ORC. 3,4,[14][15][16] Similar to previous reports, 5-year relapse-free survival, cancer-specific survival and overall survival were stratified into pT and pN, and the presence or absence of lymph node dissection, pT and pN were significant factors associated with recurrence on multivariate analysis. Whether MIRC increases port-site recurrence or disseminated abdominal recurrence, such as carcinomatous peritonitis, is highly controversial.…”
Section: Discussionsupporting
confidence: 73%
“…Fujimura reviewed robot‐assisted radical cystectomy (RARC) for bladder cancer . In this study, the author comprehensively described many issues, including the worldwide spread of RARC, patient selection, preoperative management, surgical procedures, lymph node dissection, urinary diversion (UD), complications, oncological outcomes, patterns of recurrence, educational programs, cost and future perspectives.…”
mentioning
confidence: 99%
“…Although RARC is becoming widespread, there are many points that should be discussed, as described by Fujimura . Of these, the choice of the procedure for UD, extracorporeal or intracorporeal (ICUD), is an important point in RARC.…”
mentioning
confidence: 99%
See 1 more Smart Citation